(untitled) (Scientific journal of the Fergana State University, 2023)
The article provides an ecological and faunistic analysis of sucking insects living on gymnosperms in the conditions of the Ferghana Valley. On gymnosperms and shrubs, 7 species of aphids and 2 species of lizards were noted. Among them, Cinara pinicola, Carulaspis visci and Carulaspis minima were recorded from shields for the first time in the Ferghana Valley. According to the degree of attachment of sucking insects to forage plants, species with a one-stage nutritional spectrum (Cinara picea, Eulachnus alticola, E.tauricus, Carulaspis minima, C.visci) and species with a two-stage nutritional spectrum (Cinara tujafilina) are divided into ecological niches. Studies have been conducted on the biology and ecological characteristics of important species of aphids and lizards. Preliminary results on the study of pest entomophages have been obtained.